Berry production drives bottom–up effects on body mass and reproductive success in an omnivore. Issue 2 (22nd June 2017) - Hertel, Anne G.; Bischof, Richard; Langval, Ola; Mysterud, Atle; Kindberg, Jonas; Swenson, Jon E.; Zedrosser, Andreas
Abstract : Obligate herbivores dominate studies of the effects of climate change on mammals, however there is limited empirical evidence for how changes in the abundance or quality of plant food affect mammalian omnivores. Omnivores can exploit a range of different food resources over the course of a year, but they often rely on seasonally restricted highly nutritious fruiting bodies during critical life stages. Brown bears Ursus arctos in Sweden are dependent on berries for fattening before entering hibernation. We used a ten‐year time series to evaluate the effect of temperature and snow on annual variation in berry abundance and how this variation affected bears. We found marked interannual variation in berry production of bilberry Vaccinium myrtillus and lingonberry V. vitis‐idaea, that we could attribute in part to temperature during plant dormancy and flowering and precipitation during fruit ripening. Both, autumn weights of female bears and spring weights of yearling bears increased linearly with bilberry abundance. When bilberry abundance was low, lightweight female bears had a lower reproductive success than females in better condition. This effect vanished when food abundance was above average, indicating that lightweight females could compensate for their initial weight during good bilberry years. Our study highlights the importance of considering individuals' dynamic responses to variation in food availability, which leave some more vulnerable to food shortage than others. Individual life‐history heterogeneity in response to resource variation likely affects long‐term population recruitment. Our findings emphasize that Scandinavian bears can be dependent on a single food resource during a critical period of the year and are therefore less resilient to environmental change than expected for an omnivore. Future climate scenarios predict ambiguous trends for weather covariates that affected crucial stages of berry phenology, preventing a clear prognosis of how climate change may affect long‐term bilberry production.